2017
DOI: 10.1142/s0219581x1750017x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Reactivity of Nanostructured Zero-Valent Iron Particles for Degradation of Azo Dyes

Abstract: Nanostructured zero-valent iron (NSZVI) particles were synthesized by the method of ferric ion reduction with sodium borohydride with subsequent drying and passivation at room temperature in technical grade nitrogen. The obtained sample was characterized by means of X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy and dynamic light scattering studies. The prepared NSZVI particles represent 100–200[Formula: see text]nm aggregates, which consist of 20–30[Formula: see text]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Azo-dyes are the largest type of synthetic dyes with azo (-NN-) functional group or chromophore, which is fairly stable and recalcitrant to degradation . The degradation of azo-dyes is one of the most important reaction in the treatment of environmental pollution and industrial wastewater. , Currently, zerovalent metals have been extensively exploited in this reaction because of their low cost and high degradation capability. , Fe- and Mg-based metallic catalysts are the typical zerovalent metals for the degradation of azo-dyes. Unfortunately, the stability of these catalysts is still unsatisfactory.…”
Section: Catalysis Of Heasmentioning
confidence: 99%
“…Azo-dyes are the largest type of synthetic dyes with azo (-NN-) functional group or chromophore, which is fairly stable and recalcitrant to degradation . The degradation of azo-dyes is one of the most important reaction in the treatment of environmental pollution and industrial wastewater. , Currently, zerovalent metals have been extensively exploited in this reaction because of their low cost and high degradation capability. , Fe- and Mg-based metallic catalysts are the typical zerovalent metals for the degradation of azo-dyes. Unfortunately, the stability of these catalysts is still unsatisfactory.…”
Section: Catalysis Of Heasmentioning
confidence: 99%
“…It was shown previously that zero valent iron (ZVI) is efficient for the removal of recalcitrant organic compounds [25] and heavy metals [26,27]. We have shown that the ZVI can be used for the decomposition of azo dyes [28] and as a Fenton-like zinc removal catalyst [29]. In a majority of research works on this topic, borohydride-reduced iron was used as a waste treatment material.…”
mentioning
confidence: 99%
“…nZVI particles showed superior efficiency in the removal of antibiotics [27], phenolic compounds [28], heavy metals [29,30], inorganic pollutants [31], and organic dyes [32,33]. Our previous studies showed that nZVI particles are very effective for the decomposition of azo dyes [34] and as a fenton-like zinc removal catalyst [35]. nZVI have a higher reaction rate because of their very high specific surface area and surface energy for the redox process [36].…”
mentioning
confidence: 99%